Stroke mortality attributable to high red meat intake in China and South Korea: An age–period–cohort and joinpoint analysis - Chen, Fangyao; Hu, Weiwei; Chen, Shiyu; Si, Aima; Zhang, Yuxiang; Ma, Jiaojiao (Frontiers in Nutrition, 2022)
The high intake of red meat is well recognized as a major health concern worldwide. It has been recognized as a risk factor for several non-communicable chronic diseases including stroke. However, previously published studies have not provided a comprehensive analysis of the long-time trend of stroke mortality attributable to high red meat intake in China and South Korea, two countries with similar dietary patterns and changing trends. Therefore, this study aimed to reveal the influence of age, time period, and birth cohort on long-term trends of stroke mortality attributable to high red meat intake and relative gender differences in China and South Korea. Data were obtained from the Global Burden of Disease 2019 database. The age-period-cohort model was performed to estimate the effect of age, time period, and birth cohort. The average and annual percent changes were estimated through the Joinpoint regression. Results indicated that the overall attributable age-standardized mortality rates of stroke in China decreased by 1.0% (P<0.05) for females and 0.1% (P>0.05) for males, compared with a decrease of 4.9% for females and 3.7% for males in South Korea (both P<0.05). Age-period-cohort analysis revealed that the attributable stroke mortality decreased along with the time period, and increased along with age. Significant gender differences were observed, males in both countries were at higher risk than females, especially in China. Joinpoint analysis suggested that the attributable stroke mortality for both genders in South Korea and females in China showed a decreasing trend, while it is stable for males in China. Although prominent reductions were observed during the past decades, the attributable stroke mortality risk in China and South Korea is still high. Our findings indicate that controlling the intake of red meat may be a cost-effective strategy to reduce stroke mortality risk and the corresponding disease burden, especially for Chinese males.